CROSSWORD GAME IN IMPROVING STUDENTS’ ENGLISH VOCABULARY - Sitti Nurjannah; Rizka Indahyanti; Putri Handayani (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2023)
This study is to investigate whether or not students' vocabulary may be improved through the use of crossword puzzles. The participants in this study were students from class VII of SMPN 16 Makassar, which is divided into two classes: VII-4, which served as the experimental class, and VII-6, which served as the control class. Each class has a total of twenty-three students. As a result of receiving treatment, the results demonstrated that the score was in an excellent position. After taking the test, students in the experimental class had an average score of 88.13, which was significantly higher than their pre-test score of 76.47. On the other hand, the average score for the control class before the test was 59.95, and the average score after the test was 66.86. It has been determined that the utilization of crossword puzzles is effective in enhancing the English vocabulary of students in the seventh grade at SMPN 16 Makassar.